Visual analysis of low-carbon supply chain: Development, hot-spots, and trend directions - Luo, Jianli; Huang, Minmin; Bai, Yanhu (Frontiers in Environmental Science, 2022)
A low-carbon supply chain is generally a clean practice to achieve carbon peak and carbon neutralization; it transforms supply chain management into a green economy, aiming to reduce energy consumption, reduce pollution and achieve sustainable development in all parts of the supply chain. However, there have been few specific reviews of low-carbon supply chains to date. Therefore, this article provides a comprehensive analysis of the literature on low-carbon supply chains and explores the current knowledge system, evolution trend of topics, and future research directions, and enriches the green economy framework. A systematic analysis was conducted using bibliometric and content analysis. A total of 1,811 articles from 2003 to 2021 were selected, discussed, and analyzed. We found that low carbon supply chain is a growing research topic. We also identified influential authors, the geographical distribution of articles, and subject categories in this field. Next, we defined five clusters using exhaustive content analysis and explored the evolution trend of significant topics. Finally, we proposed a future research agenda for low-carbon supply chains as well as to further deepen the knowledge structure of the green economy.